2019
DOI: 10.1186/s13021-019-0132-x
|View full text |Cite
|
Sign up to set email alerts
|

How can forest management increase biomass accumulation and CO2 sequestration? A case study on beech forests in Hesse, Germany

Abstract: Background: While the capability of forests to sequester carbon dioxide (CO 2) is acknowledged as an important component in fighting climate change, a closer look reveals the difficulties in determining the actual contribution by forest management when indirect and natural impacts are to be factored out. The goal of this study is to determine the direct human-induced impacts on forest growth by cumulative biomass growth and resulting structural changes, exemplified for a dominating forest species Fagus sylvati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
6
0
1
Order By: Relevance
“…Halpin and Lorimer (2016) have shown that, in the later stages of old growth, biomass may indeed decline. These results have led to diverging positions regarding the climate protection potential of naturally developing unmanaged forests (Griscom et al., 2017; Höltermann et al., 2020; Jandl et al., 2019; Krug, 2019; Kun et al., 2020; Schulze et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Halpin and Lorimer (2016) have shown that, in the later stages of old growth, biomass may indeed decline. These results have led to diverging positions regarding the climate protection potential of naturally developing unmanaged forests (Griscom et al., 2017; Höltermann et al., 2020; Jandl et al., 2019; Krug, 2019; Kun et al., 2020; Schulze et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Los bosques coadyuvan a mitigar el cambio climático global mediante el almacenamiento de carbono en la vegetación y en el suelo, así como en el intercambio con la atmósfera. La creciente preocupación y demanda por llevar a cabo estudios de biomasa posibilita comprender el funcionamiento de los bosques y, a su vez, entender cómo los cambios de uso del suelo pueden alterar la estructura, biodiversidad y los servicios ecosistémicos; esto último podría ser revertido o atenuado mediante un adecuado manejo (Krug, 2019;Mori et al, 2017;Tong et al, 2020). Los bosques se destacan por su gran capacidad de fijar carbono en sus estructuras leñosas (Trugman et al, 2018); pues, el fuste de un árbol almacena aproximadamente el 84 % de biomasa, de la cual el 46 % es carbono (Tobías-Baeza et al, 2019).…”
Section: Introductionunclassified
“…Comparisons based on stands of a similar age (Bouriaud et al., 2019), or range in ages (Krug, 2019), or over a rotation period (Klein et al., 2013), do not reflect fully the impact of human activities on the forest age distribution and, therefore, the total ecosystem carbon stocks or the characteristics of ecosystems that maintain stable stocks. Landscape‐scale metrics (S1) are more appropriate as they account for the spatial scales at which ecological and evolutionary processes and natural disturbance regimes operate, such as described by Net Biome Production (Schulze et al., 2000).…”
Section: Factors Influencing Evaluation Of Mitigation Effectivenessmentioning
confidence: 99%
“…The mutual reinforcing of climate change and biodiversity loss means that assessment of mitigation strategies needs to consider the consequences for biodiversity (Pörtner et al., 2021). Investment in emissions reduction activities, particularly related to forest management, can result in poor mitigation and conservation outcomes if decisions are based on inappropriate comparisons related to the land area, use of reference levels, and time horizons (Klein et al., 2013; Bouriaud et al., 2019; Krug, 2019), which result in flawed analyses. Such analyses fail to properly reveal the actual change in the atmospheric carbon stock of different activities at the land areas and time horizons relevant for decision making.…”
Section: Introductionmentioning
confidence: 99%